Population genomics reveal deep divergence and strong geographical structure in gentians in the Hengduan Mountains - Fu, Peng-Cheng; Sun, Shan-Shan; Hollingsworth, Peter M.; Chen, Shi-Long; Favre, Adrien; Twyford, Alex D. (Frontiers in Plant Science, 2022)
Understanding the evolutionary and ecological processes driving population differentiation and speciation can provide critical insights into the formation of biodiversity. Here, we examine the link between population genetic processes and biogeographic history underlying the generation of diversity in the Hengduan Mountains (HM), a region harbouring a rich and dynamic flora. We used restriction site associated DNA sequencing to generate 1,907 single nucleotide polymorphisms (SNPs) and four-kb of plastid sequence in species of the Gentiana hexaphylla complex (Gentianaceae). We performed genetic clustering with spatial and non-spatial models, phylogenetic reconstructions, and ancestral range estimation, with the aim of addressing the processes influencing diversification of G. hexaphylla in the HM. We find the G. hexaphylla complex is characterised by geographic genetic structure with clusters corresponding to the South, North and the central HM. Phylogenetic reconstruction and pairwise FST analyses showed deep differentiation between Southern and Northern populations in the HM. The population in Mount Taibai exhibited the highest genetic similarity to the North HM. Ancestral range estimation indicated that the G. hexaphylla complex originated in the central HM and then diverged in the Pliocene and the Early Pleistocene, before dispersing widely, resulting in the current distinct lineages. Overall, we found deep genomic differentiation in the G. hexaphylla complex corresponds to geographic barriers to dispersal in the HM, and highlight a critical role of the uplift of the Daxue Mountains and subsequent climatic fluctuations underlying diversification. The colonization of G. hexaphylla in the Mount Taibai region suggests a directional dispersal between the alpine flora of the Qinling and the HM.